Earthquake-Induced Domino-Type Progressive Collapse in Regular, Semiregular, and Irregular Bridges - Amir Seyedkhoei; Reza Akbari; Shahrokh Maalek (Shock and Vibration)
Progressive collapse is a persistent spread and enlargement of initial local failure of structures characterized by inconsistency between the initial failure and its resulting extensive collapse. Although, great contributions have been made towards the progressive collapse of building structures, comparably small attention has been paid to bridge structures. In this study, the procedure of progressive collapse of bridges with concrete prestressed voided slab under earthquakes and effects of other parameters on propagation of collapse of regular, semiregular, and irregular bridges are investigated. At first, a bridge specimen, which its shake table test results were provided by previous researchers, was modeled and verified using the applied element method. Then, the progressive collapse of the box girder bridge was investigated. In the next step, progressive collapse process of the same bridge with posttensioned voided slab under earthquakes was studied using nonlinear time history analysis. Irregularities of the piers were analyzed parametrically. The results show that domino-type progressive collapse happens in bridges with voided slab after the initial failure of the deck at the seating of bridge abutment. Also, it is concluded that, type of the deck, height of the piers, and ground slope have a great effect on the progressive collapse procedure of both regular and irregular bridges with voided slab deck.